Entrepreneurship development in public enterprises - Prokopenko, Joseph; Pavlin, Igor.; International Labour Office; International Center for Public Enterprises in Developing Countries (Geneva : International Labour Office ; Ljubljana : International Center for Public Enterprises in Developing Countries, 1991)
This book presents a number of cases in which the culture and practice of entrepreneurship were successful introduced into the structure and activities of public enterprises. Includes here are two cases of public entrepreneurship within a centrally planned system.
Includes bibliographical references (p. 199-208).
hza 02/08/2018
Loans
Keywords: Public enterprises; Entrepreneurship